PENGARUH NON PERFORMING LOAN (NPL), LOAN TO DEPOSIT RATIO (LDR) DAN NET INTEREST MARGIN (NIM) TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN PERBANKAN - Kemal Wira Fasha; Abdul Rauf Chaerudin (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The purpose of this study was to determine the effect of Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Return On Assets (ROA) either partially or simultaneously in banking companies listed on the Indonesia Stock Exchange. . This study uses a quantitative approach with secondary data in the form of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) and Return On Assets (ROA). Determination of the sample in this study using purposive sampling technique with 3 criteria in order to obtain 5 companies from 46 companies. The analysis technique used is a data regression analysis technique using the SPSS Version 25 application. The results of data processing show that the data is normally distributed and there are no symptoms of classical assumptions in the study. The conclusion obtained shows that Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR) partially have a negative and significant effect on Return On Assets (ROA). Net Interest Margin (NIM) partially positive and significant effect on Return On Assets (ROA). And simultaneously there is the influence of Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Return On Assets (ROA).